Ordine temporale e ordine spirituale nella riflessione di Aldo Moro: una lezione sottratta all’oblio (Stato, Chiese e pluralismo confessionale, 2017)
Contributo sottoposto a valutazioneSOMMARIO: 1. Le carte e la storia – 2. Frammenti di una lezione: schemi di rapporti tra Stato e Chiesa – 3. Influenze sturziane sulla costruzione giusfilosofica di Aldo Moro – 4. Storia e memoria per una ricerca in progress - Appendice.ABSTRACTIn 1978 thanks to the heirs and the "A. Moro" Foundation it was published the monograph: A. Moro, Lezioni di filosofia di diritto tenute presso l’ Università di Bari. Il diritto 1944-45- appunti sull’esperienza giuridica: lo Stato 1946-47, Published by Cacucci of Bari. The work collects the lectures presented by the statesman at the University of Bari for a series of legal philosophy lessons during the academic years 1944-45 and 1946-47. The volume partially reproduces the original text, published many years before, in lithographed volumes, by another publisher. In the posthumous edition the chapter about ‘Church and State’ has been omitted.For the ecclesiastical science researcher, Aldo Moro’s considerations about the relationship between church and state appear unavoidable. The inexplicably obliterated pages are still applicable to these days, especially if compared to the contribution made by Moro during the Constituent Assembly for the final draft of the Articles 7 and 8 of the Constitution. This study aims to go beyond the limits of an arid archival recovery, it not only aims to interpret the cultural dimension of the future constituent deputy, but it aims to identify the doctrinal sources that the young Moro used for his reflections about the relationships between Church and State.